The effect of ventricular volume increase in the amplitude of intracranial pressure. Issue 9 (4th July 2019) - Apura, João; Tiago, Jorge; Bugalho de Moura, Alexandra; Lourenço, José Artur; Sequeira, Adélia
Abstract: We study the impact of vascular pulse in the cerebrospinal fluid (CSF) pressure measured on the lateral cerebral ventricles, as well as its sensitivity with respect to ventricular volume change. Recent studies have addressed the importance of the compliance capacity in the brain and its relation to arterial pulse abortion in communicating hydrocephalus. Nevertheless, this mechanism is not fully understood. We propose a fluid-structure interaction (FSI) model on a 3 D idealized geometry based on realistic physiological and morphological parameters. The computational model describes the pulsatile deformation of the third ventricle due to arterial pulse and the resulting CSF dynamics inside brain pathways. The results show that when the volume of lateral ventricles increases up to 3.5 times, the amplitudes of both average and maximum pressure values, computed on the lateral ventricles surface, substantially decrease. This indicates that the lateral ventricles expansion leads to a dumping effect on the pressure exerted on the walls of the ventricles. These results strengthen the possibility that communicant hydrocephalus may, in fact, be a natural response to reduce abnormal high intracranial pressure (ICP) amplitude. This conclusion is in accordance with recent hypotheses suggesting that communicant hydrocephalus is related to a disequilibrium in brain compliance capacity.